PRMT1 promotes extracellular matrix degradation and apoptosis of chondrocytes in temporomandibular joint osteoarthritis via the AKT/FOXO1 signaling pathway. (December 2021) - Shen, Qinhao; Xiao, Yiwen; Cheng, Bei; Sun, Zheyi; Hu, Yu; Yang, Hefeng; Luo, Yingwei
Abstract: Temporomandibular joint osteoarthritis (TMJOA) is a chronic degenerative joint disease characterized by extracellular matrix (ECM) degradation and chondrocyte apoptosis. The aim of this study was to investigate the role of PRMT1 in TMJOA pathogenesis and its underlying molecular mechanism. Compared to the control group, PRMT1 was highly expressed in IL-1β-treated chondrocytes and articular cartilage following MIA injection into rat TMJs. Furthermore, knocking down PRMT1 considerably inhibited ECM degradation and apoptosis induced by IL-1β. Mechanistic analyses further revealed that PRMT1 knockdown activated the PI3K/AKT signaling pathway and prevented FOXO1 from translocating to the nucleus. Moreover, an inhibitor of AKT (LY294002) rescued the effect of PRMT1 knockdown on IL-1β-induced ECM degradation and apoptosis, and AMI-1, a selective inhibitor of PRMT1, inhibited PRMT1 expression and reversed the pathological progress of TMJOA. Thus, our findings suggest that PRMT1 plays an essential role in ECM degradation and chondrocyte apoptosis in TMJOA via the AKT/FOXO1 signaling pathway. Highlights: TMJOA leads to extracellular matrix degradation and chondrocyte apoptosis. MIA injections can lead to TMJOA development. PRMT1 was upregulated in IL-1β-treated chondrocytes. PRMT1 was significantly upregulated in articular cartilage after MIA injection. PRMT1 inhibition alleviates TMJOA-associated pathology via AKT/FOXO1 signaling.